2016
DOI: 10.1111/ijfs.13141
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of matrix and gene marker on the real‐time PCR detection of wheat

Abstract: Summary DNA‐based methods have been advanced as excellent alternatives for the detection and quantification of gluten‐containing cereals. In this study, it was intended to evaluate the effect of three distinct food matrices on the performance three TaqMan real‐time PCR approaches targeting α2‐gliadin, agglutinin isolectin (Tri a 18) and thioredoxin h(Tri a 25) genes of wheat. The results of wheat flour detection in soya bean, maize and rice model matrices evidenced that sensitivity was considerably affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…is proves the significant role of the DNA marker in the GMO detection. Our findings coincide with the results of Martin-Fernaandez et al [37]. ey have reported that the sensitivity of the detection of wheat was considerably affected by the marker gene.…”
Section: Impact Of Heat On the Gmo-specific Ampliconssupporting
confidence: 93%
“…is proves the significant role of the DNA marker in the GMO detection. Our findings coincide with the results of Martin-Fernaandez et al [37]. ey have reported that the sensitivity of the detection of wheat was considerably affected by the marker gene.…”
Section: Impact Of Heat On the Gmo-specific Ampliconssupporting
confidence: 93%
“…Moreover, the LOD of raw sausages is 0.005% (50 mg/kg, w/w) with optimal PCR performance parameters (R 2 = 0.990, slope = −3.122, and PCR efficiency = 109.1%), contrarily to raw ham that achieved a LOD of 0.01% (100 mg/kg, w/w) and a correlation coefficient of 0.951, below the acceptable value of 0.98 (Figure 3c, Table 2). The effect of food matrix in food allergen detection by DNA-based methods has been reported by some authors [18,29,30]. The use of reference materials with different calibration models in order to simulate the real food matrices is extremely important.…”
Section: Effect Of Food Matrix and Thermal Treatmentmentioning
confidence: 99%
“…This technique is highly sensitive (5–50 pg of DNA) and can lead to species identification (useful for cross-contamination studies). Real time PCR methods can be also used for the quantitative detection of gluten when using model mixtures [ 46 , 47 ]. Moreover, PCR methods perform indirect detection (not pathogenic compounds of gluten—rather the DNA that codifies for it) [ 48 ].…”
Section: Methods For Gluten Detection In Food Samplesmentioning
confidence: 99%